(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article proposes the use of green roofs as a solution to the global socio-ecological problems caused by the increase in the level of urbanization, and the experience of Western countries is analyzed in order to implement this idea in the regions of Central Asia.